Heat Transfer in Solar Thermochemical Reactor Using Taguchi’s Method - Vikram Kumar (AG Volumes, 2021)
Solar-driven thermochemical reaction systems utilising concentrated solar radiation for the synthesis of syngas and hydrogen (primarily CO and H2) are now widely regarded as a viable alternative to conventional fossil fuels in solving energy and climate change issues. Thermal analysis of a thermochemical reactor system is the subject of this study. During the study, several situations of porosity, fluid medium entry velocity, and solar irradiation intensity are taken into account. In order to discover the optimal configuration for porosity, intake velocity, and solar irradiance for the full reactor system, the Taguchi L27 orthogonal approach was used.